Penerapan Model Pembelajaran Kooperatif Numbered Head Together (NHT) terhadap Hasil Belajar Siswa Pada Mata Pelajaran Biologi Materi Ekosistem Di Sma Negeri 1 Limboto Barat - Yudit O. R. Rumbekwan; Lilan Dama; Abubakar Sidik Katili (Research Review: Jurnal Ilmiah Multidisiplin, 2023)
This research is an experimental research that aims to determine the effect of the Numbered Head Together (NHT) learning model on biology learning outcomes of SMA N 1 Limboto Barat, Gorontalo on ecosystem material with the Nonequivalent Control Group Design research design. The population in this study consisted of three classes, namely class X MIPA 1 with a total of 20 students and X MIPA 19 with a total of 30 students as an experimental class and class X IPS 1 with a total of 14 students as a control class. The research variable consists of the independent variable, namely the use of Number Head Together (NHT), while the dependent variable is student learning outcomes. Data collection was carried out through pre-test and post-test. Based on the results of the study, it was shown that the average post-test learning outcomes for students in class X MIPA 1 and X MIPA 2 as an experimental class taught using the Numbered Heads Together (NHT) model, obtained an average result of 74.92, while the results the average learning obtained by students of class X IPS 1 as a control class taught using the conventional model is 51.12. Furthermore, the control class experienced an increase in student graduation by 21%, while the experimental class experienced an increase in student graduation by 64%, which means that the value of student learning outcomes increased more than threefold with the treatment of using the Numbered Heads Together (NHT) model, especially in the experimental class.